2011
DOI: 10.1038/sj.bjc.6606065
|View full text |Cite
|
Sign up to set email alerts
|

The semisynthetic flavonoid monoHER sensitises human soft tissue sarcoma cells to doxorubicin-induced apoptosis via inhibition of nuclear factor-κB

Abstract: Background:Despite therapeutic advances, the prognosis of patients with metastatic soft tissue sarcoma (STS) remains extremely poor. The results of a recent clinical phase II study, evaluating the protective effects of the semisynthetic flavonoid 7-mono-O-(β-hydroxyethyl)-rutoside (monoHER) on doxorubicin-induced cardiotoxicity, suggest that monoHER enhances the antitumour activity of doxorubicin in STSs.Methods:To molecularly explain this unexpected finding, we investigated the effect of monoHER on the cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This may be through its ability to reduce production of the cardiotoxic metabolite DOXOL. MonoHER has also been shown to potentiate the cytotoxicity of DOX in human liposarcoma cells by reducing NF-κB activation and promoting DOX-induced apoptosis [ 143 ]. In vitro and in vivo experiments have shown that monoHER does not interfere with the anti-tumor effect of DOX.…”
Section: Strategies To Improve Clinical Response And/or Reduce Clinicmentioning
confidence: 99%
“…This may be through its ability to reduce production of the cardiotoxic metabolite DOXOL. MonoHER has also been shown to potentiate the cytotoxicity of DOX in human liposarcoma cells by reducing NF-κB activation and promoting DOX-induced apoptosis [ 143 ]. In vitro and in vivo experiments have shown that monoHER does not interfere with the anti-tumor effect of DOX.…”
Section: Strategies To Improve Clinical Response And/or Reduce Clinicmentioning
confidence: 99%
“…Targeting NF-κB signaling pathways might thus be effective in treating Ras-mutated tumors. Interestingly, NF-κB inhibition by dehydroxymethylepoxyquinomicin inhibited proliferation, decreased mitotic index, and triggered apoptosis of OS cells (Castro-Gamero et al 2012), while the semisynthetic flavonoid 7-mono-O-(β-hydroxyethyl)-rutoside potentiated the antitumor activity of doxorubicin in human LS cells (Jacobs et al 2011).…”
Section: Pathobiologymentioning
confidence: 99%
“…Interestingly, the antimicrobial fish peptide pardaxin exhibited antitumor activity toward murine FS by downregulating STAT-3 and p65/RelA (Wu et al 2012). A clinical phase II study with metastatic cancer patients, evaluating the protective effects of the semisynthetic flavonoid 7mono-O-(β-hydroxyethyl)-rutoside on doxorubicin-induced cardiotoxicity, revealed a 75 % response rate in STS patients (Bruynzeel et al 2007), most probably via inhibition of NF-κB (Jacobs et al 2011). Curcumin from turmeric inhibited growth of LMS and OS cells via inhibition of PI3K/AKT/mTOR and Notch-1, respectively (Wong et al 2011;Li et al 2012b) and induced apoptosis and cell cycle arrest in ES cells (Singh et al 2010).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…This has not been observed in animals thus far 15 . MonoHER has been shown to sensitize cancer cells to apoptosis by preventing doxorubicin‐induced NF‐κB activation 40 . The possible contribution of metabolites to this potentiating effect of monoHER has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%